2010
DOI: 10.1007/s00125-010-1819-4
|View full text |Cite
|
Sign up to set email alerts
|

Tadalafil increases muscle capillary recruitment and forearm glucose uptake in women with type 2 diabetes

Abstract: Aims/hypothesisRecent evidence suggests that reduced synthesis of nitric oxide in endothelial cells, i.e. endothelial dysfunction, contributes to the impaired action of insulin in the vasculature of patients with type 2 diabetes. We investigated whether selective inhibition of phosphodiesterase-5 by tadalafil has beneficial effects on peripheral microcirculation and glucose uptake in these patients.MethodsWe enrolled seven postmenopausal women with type 2 diabetes and ten age-matched healthy women as controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 10 publications
2
28
0
Order By: Relevance
“…Consistent with data reported in the pilot study conducted by Grover-Páez et al 20 with sildenafil, a lowering of HbA 1c upon treatment with PF-00489791 was also observed in the present study. Although the precise mechanism of HbA 1c reduction upon inhibition of PDE5 is unclear, preclinical and clinical studies suggest that PDE5 inhibition may favorably impact glucose metabolism in T2DM by mediating enhanced glucose uptake in skeletal muscle 22,23 improving b-cell function and decreasing insulin resistance. [24][25][26] Such mechanisms may eventually contribute to the improvement in microvascular disease and subsequent reduction of albuminuria in studies of longer treatment duration with PF-0048971.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with data reported in the pilot study conducted by Grover-Páez et al 20 with sildenafil, a lowering of HbA 1c upon treatment with PF-00489791 was also observed in the present study. Although the precise mechanism of HbA 1c reduction upon inhibition of PDE5 is unclear, preclinical and clinical studies suggest that PDE5 inhibition may favorably impact glucose metabolism in T2DM by mediating enhanced glucose uptake in skeletal muscle 22,23 improving b-cell function and decreasing insulin resistance. [24][25][26] Such mechanisms may eventually contribute to the improvement in microvascular disease and subsequent reduction of albuminuria in studies of longer treatment duration with PF-0048971.…”
Section: Discussionmentioning
confidence: 99%
“…However, we were unable to demonstrate any acute eff ect on either vascular function or glucose uptake of the phosphodiesterase-5 (PDE-5) inhibitor tadalafi l. because NO promotes vasorelaxation by increasing the levels of cyclic guanosine monophosphate, that is normally degraded by PDE-5. We showed that tadalafi l increases permeability surface area for glucose, as well as forearm glucose uptake in type 2 diabetes patients [ 15 ] , suggesting PDE-5 inhibition as a novel candidate for treatment of type 2 diabetes. Interestingly, that study was performed after fasting overnight and not in states of moderately elevated glucose and insulin levels as usually observed following a meal.…”
Section: Decreased Permeability Surface Area For Glucose In Obese Wommentioning
confidence: 98%
“…Recent work from our laboratory showed that an intrabrachial infusion of methacholine, a potent stimulator of NO, improves forearm PS glu and glucose uptake in obese insulin-resistant subjects after an OGTT [ 14 ] , although forearm muscle blood fl ow was unchanged. Further, aiming to evaluate the metabolic eff ects of an amplifi ed NO-signal, the phosphodiesterase-5 (PDE-5)-inhibitor tadalafi l was tested in type 2 diabetes patients [ 15 ] . Inhibition of PDE-5 may result in improved microvascular function Introduction ▼ Type 2 diabetes is characterized by a combination of insulin resistance and impaired insulin secretion [ 1 ] .…”
Section: Decreased Permeability Surface Area For Glucose In Obese Wommentioning
confidence: 99%
“…It is degraded by phosphodiesterase (PDE) isoenzymes, a heterogeneous group of hydrolytic enzymes. PDE5 inhibition should thus result in an increased NO signal and improved vascular function (23). To date, eleven different PDE families have been identified, each typically having several different isoforms and splice variants.…”
Section: Mechanism Of Action Of Phosphodiesterase Type 5 Inhibitorsmentioning
confidence: 99%
“…Treatment with tadalafil in elderly women for its metabolic and micro-vascular effects on skeletal muscle and adipose tissue in type 2 diabetic patients (23), for the treatment of pulmonary hypertension (30). Little evidence is reported on its efficacy in the treatment of FSD, specially in particular populations such as women treated with antidepressant drugs (31) or women affected by type 1 Diabetes Mellitus (DM) with sexual arousal disorders (28).…”
Section: Tadalafilmentioning
confidence: 99%